2014
DOI: 10.1371/journal.pone.0101110
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Dynamics of Dry Lamellar Crystals of Sugar Based Lipids: An Atomistic Simulation Study

Abstract: The rational design of a glycolipid application (e.g. drug delivery) with a tailored property depends on the detailed understanding of its structure and dynamics. Because of the complexity of sugar stereochemistry, we have undertaken a simulation study on the conformational dynamics of a set of synthetic glycosides with different sugar groups and chain design, namely dodecyl β-maltoside, dodecyl β-cellobioside, dodecyl β-isomaltoside and a C12C10 branched β-maltoside under anhydrous conditions. We examined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…There have been several experimental studies involving glycolipids that can adopt similar lamellar phases, but most rely on synthesizing small libraries of molecules to uncover the desired nanostructures. Moreover, molecular simulations are rare for these systems and usually focus on understanding and rationalizing experimental results . Here we describe a computational prediction of an amphiphilic molecule that could achieve the desired small spacings and the subsequent preparation of a bespoke sample to verify the prediction.…”
Section: Results and Discussionmentioning
confidence: 99%
“…There have been several experimental studies involving glycolipids that can adopt similar lamellar phases, but most rely on synthesizing small libraries of molecules to uncover the desired nanostructures. Moreover, molecular simulations are rare for these systems and usually focus on understanding and rationalizing experimental results . Here we describe a computational prediction of an amphiphilic molecule that could achieve the desired small spacings and the subsequent preparation of a bespoke sample to verify the prediction.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Figure 4 shows the possible locations of the HBO probes. The association of the sugar group with the lipophilic moiety is made possible by the sugar amphoteric nature via the saccharide hydrophobic face 52 53 , thus stabilizing the mostly hydrophobic backbone of HBO. In a related study, Loura and Ramalho reported that when labelling 1,2-dipalmitoyl- sn -glycero-3-phosphocholine (DPPC) bilayers with 7-nitrobenz-2-oxa-1,3-diazol-4-yl (NBD) acyl-chain as a fluorescent probe, the NBD fluorophore adopts a transverse location closer to the water/lipid interface than to the center of the bilayer 54 .…”
Section: Resultsmentioning
confidence: 99%
“…16 Therefore, dynamic investigation of the anhydrous systems is timely to support the growing scientific interest in the thermotropic lipidic phases from the seminal work of Jeffrey 17 and more recently those of Ericsson et al 18 and Auvray et al 19 Considering these points, we have concentrated our efforts on studying the thermotropic glycolipid phases in the absence of a solvent. 20,21 In addition, we have also previously reported on the pyroelectric behavior in dry glycolipids. 22 In the ensuing study here, we have investigated the dielectric properties of Guerbet maltosides to establish the diffusion mechanism and the dynamic of the materials without the solvent effect.…”
Section: Fig 1 (A)mentioning
confidence: 93%